1992
DOI: 10.1095/biolreprod47.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Content of Insulin-like Growth Factors in Porcine Oviductal Fluid1

Abstract: Oviductal fluid (OvF) was collected from gilts by indwelling catheters during the estrous cycle and analyzed for content of insulin-like growth factors (IGF-I, IGF-II). Group 1, composed of 9 gilts in a summer environment near a boar, yielded mean daily fluid volumes of 1.18 +/- 0.16 ml during estrus and 0.69 +/- 0.03 ml post-estrus. Group 2, composed of 7 gilts in a moderate-temperature, light-regulated room, yielded 1.20 +/- 0.18 ml during estrus and then OvF flow essentially stopped. Serum samples were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 17 publications
1
32
1
3
Order By: Relevance
“…An explanation for the differences in plasma IGF-I concentration observed 12 to 24 h after ovulation could be that nutritionally-induced changes in folliculogenesis, although not evident in the period of follicular recruitment [3], could be further augmented during the later stages of preovulatory follicular growth. However, it is unlikely that differences in ovarian IGF-I could contribute to the differences found in this study, since previous studies have been unable to link serum IGF-I concentrations to the estrous cycle [29]. Irrespective of gilt or treatment in Experiment 3, IGF-I concentrations in oviduct plasma and oviduct flushings were related.…”
Section: Oviduct Flushingsmentioning
confidence: 51%
See 3 more Smart Citations
“…An explanation for the differences in plasma IGF-I concentration observed 12 to 24 h after ovulation could be that nutritionally-induced changes in folliculogenesis, although not evident in the period of follicular recruitment [3], could be further augmented during the later stages of preovulatory follicular growth. However, it is unlikely that differences in ovarian IGF-I could contribute to the differences found in this study, since previous studies have been unable to link serum IGF-I concentrations to the estrous cycle [29]. Irrespective of gilt or treatment in Experiment 3, IGF-I concentrations in oviduct plasma and oviduct flushings were related.…”
Section: Oviduct Flushingsmentioning
confidence: 51%
“…Although previous studies have characterized IGF-I concentrations [29] and pOSP protein and mRNA abundance [11] during the estrous cycle, neither reported changes during the critical periovulatory period. Furthermore, because we have shown that the interval between the onset of estrus and the time of ovulation is highly variable in gilts, we believed it was critical to use the moment of ovulation as a critical reference point in these studies.…”
Section: Oviduct Flushingsmentioning
confidence: 89%
See 2 more Smart Citations
“…In bovine embryos, Prelle et al [42] demonstrated that 100 ng/ml IGF-I significantly increased blastocyst production, while it significantly decreased transcription of IGF-I receptors in the embryo. The IGF-I concentration in oviduct fluid is approximately 61 ng/ml in humans [45] and 24.7-35.3 ng/ml in pigs [46], but that in the bovine has yet to be determined. These findings suggest that a physiologically optimal concentration of IGF-I for bovine embryo development remains to be determined.…”
mentioning
confidence: 99%